Evaluation of the “Sepekan” Application Utilization by the Gresik District Government - Kholifah, Anik Nur; Samsi, Nur; Widiyawati, Wiwik; Mulyani, Endah; Musfara, Deah Dwi; Indarto, Tomi (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2025)
Improvements in the utilization of the Sepekan application within the Gresik Regency are crucial to determining the extent of its proper implementation. This study aims to assess the usage of the